2014
DOI: 10.2298/tsci110710084a
|View full text |Cite
|
Sign up to set email alerts
|

Performance of solar dryer chamber used for convective drying of sponge-cotton

Abstract: Solar dryer chamber is designed and operated for five days of July 2008. Drying experiments are conducted for sponge-cotton; as a reference drying material in the ranges between 35.0 to 49.5 °C of ambient air temperature, 35.2 to 69.8 °C drying air temperature, 30 to 1258 W/m 2 solar radiation, and 0.016 to 0.08 kg/s drying air flow rate. For each experiment, the mass flow rate of the air remained constant throughout the day. The variation of moisture ratio, drying rate, overall dryer efficiency, and temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The coffee beans' initial moisture content can be evaluated on a wet and dry basis which is stated in percent for every 60 minutes according to the following equations by Aissa, et al (2014) and Yassen et al (2016):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coffee beans' initial moisture content can be evaluated on a wet and dry basis which is stated in percent for every 60 minutes according to the following equations by Aissa, et al (2014) and Yassen et al (2016):…”
Section: Discussionmentioning
confidence: 99%
“…The drying factor must be determined to achieve the desired water content. Both Aissa et al (2014) and Dong et al (2019) have the same understanding of drying; it is a complex process that involves the transfer of heat and mass between the product and the surrounding media.…”
Section: Introductionmentioning
confidence: 99%
“…Solar drying is one possible solution but its acceptance has been limited partially due to some difficulties. A great deal of experimental work over the last few decades has already shown that agricultural products can be dehydrated using solar energy A.G.M.B.Mustayen, S.Mekhilef, R.Saidur [8] presented a paper on the study on the design, performance, and application of different types of solar dryers. The types examined are the direct, indirect, mixed-mode, active, and passive solar dryers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tzempelikos et al [42] presented an analysis of air velocity distribution in a laboratory batch-type-tray dryer. Other similar types of dryers were proposed in [43,44]. In these studies, CFD has proven to be an important simulation tool for the analysis and improvement of such dryers.…”
Section: Introductionmentioning
confidence: 99%